An Improved Method for Optimal Placement of Phasor Measurement Units in a Power Grid - Saranya C, Lakshmi priya J, Kamaraja A S (International Journal of Advanced Science and Technology, 2020)
Deregulation and growing difficulties of today's utility network have contributed to a question of the reliability of the electricity grid, which in effect has led to a number of blackouts and electricity crises. For secure operation of the power system, close monitoring of the system operating conditions using phasors is required. A PMU is a device that measures the current and voltage phase angles concerning a GPS clock pulse in a power grid during power transmissions. This paper presents an improved method for optimal placement of PMU in the power grid. It consists of two modules, the first module comprises of PMU optimization using the Gauss-Newton method, the second module comprises of PMU optimization using particle Swarm Optimization Technique. The performance of these methods is tested on the 14-bus system and IEEE 39 bus system.